Exergy loss analysis on diesel methanol dual fuel engine under different operating parameters. (1st March 2020) - Ma, Baodong; Yao, Anren; Yao, Chunde; Wu, Taoyang; Wang, Bin; Gao, Jian; Chen, Chao
Highlights: A mathematic algorithm to analyze exergy balance of dual fuel engine was built. Dual fuel engine has low heat transfer and exhaust exergy losses at high load. The quantity of exergy loss items are great affected by the intake air temperature. Higher temperature parameters reduce exergy loss in diesel methanol dual fuel engine. Abstract: In order to reveal the mechanism of high thermal efficiency of diesel methanol dual fuel (DMDF) engine, the exergy loss of DMDF engine under different operating parameters is investigated by using experimental and calculative methods based on the second law of thermodynamics. It has been found that DMDF has lower heat transfer exergy loss under all engine loads due to the high latent heat of vaporization of methanol which reduces the temperature in-cylinder. The exhaust exergy loss of DMDF under high load is relatively low compared with that of pure diesel fuel, while it is opposite to that under medium-low load. This is due to the influence of different temperatures on the incomplete combustion of methanol, which also indicates the main cause for the high thermal efficiency of DMDF under high load. Then studies on exergy analysis of DMDF under different temperatures were carried out. The studies covers the effect of intake air temperature on exergy efficiency, the heat transfer exergy loss and the exhaust physical exergy loss increase with rising intake air temperature as well. The results shows that the exhaust chemical exergy loss decreases significantly with the increase of intake air temperature and higher intake air temperature helps to improve exergy efficiency. Additionally, it is concluded that higher methanol temperature and cooling water temperature can improve exergy efficiency by decreasing exhaust exergy loss and combustion irreversible exergy loss. Finally, some feasible measures are proposed to further improve DMDF engine's performance.